A meta‐analysis of pica and micronutrient status. Issue 1 (26th August 2014) - Miao, Diana; Young, Sera L.; Golden, Christopher D.
<x xml:space="preserve">Abstract</x> Objectives Pica is the craving for and consumption of nonfood items, including the ingestion of earth (geophagy), raw starch (amylophagy), and ice (pagophagy). Pica has long been associated with micronutrient deficiencies, but the strength of this relationship is unclear. We aimed to evaluate the association between pica behavior and the risk of being anemic or having low hemoglobin (Hb), hematocrit (Hct), or plasma zinc (Zn) concentrations. Methods We systematically reviewed studies in which micronutrient levels were reported by pica status. We calculated the pooled odds ratio for anemia or weighted mean difference in Hb, Hct, or Zn concentrations between groups practicing or not practicing pica behaviors. Results Forty‐three studies including 6, 407 individuals with pica behaviors and 10, 277 controls were identified. Pica was associated with 2.35 times greater odds of anemia (95% CI: 1.94–2.85, P < 0.001), lower Hb concentration (−0.65 g/dl, 95% CI: −0.83 to −0.48 g/dl, P < 0.001), lower Hct concentration (−1.15%, 95% CI: −1.61 to −0.70%, P < 0.001), and lower Zn concentration (−34.3 μg/dl, 95% CI: −59.58 to −9.02 μg/dl, P = 0.008). Statistical significance persisted after excluding outliers and in subgroup analyses by pica type and life stage. Conclusion Pica is significantly associated with increased risk for anemia and low Hb, Hct, and plasma Zn. Although the direction of the causal relationship between pica and micronutrient deficiency is unknown, the magnitude of these relationships is comparable to other well‐recognized causes of micronutrient deficiencies. Pica warrants greater public health attention; specifically the potential physiological mechanisms underpinning the relationship between pica and micronutrient deficiencies merit further study. Am. J. Hum. Biol. 27:84–93, 2015. © 2014 Wiley Periodicals, Inc.